Event-related brain potentials elicited by semantic and syntactic anomalies during auditory sentence processing. - Faustmann A; Murdoch BE; Finnigan SP; Copland DA (Journal of the American Academy of Audiology, 2005)
The present study examined auditory event-related potential (ERP) responses to sentence-embedded syntactic (phrase structure) and semantic violations. Syntactic violations were found to elicit a centroparietal negativity peaking at around 350 msec, followed by a P600. Semantic anomalies elicited an N400 as well as a late centroparietally distributed positivity. The shorter latency and different morphology of the negativity observed in response to phrase structure violations compared to semantic anomalies indicate that the observed negativities are to some extent functionally different, suggesting that phrase structure information is processed prior to lexical-semantic information. The finding of a P600 in response to semantic anomalies suggests that the latter component reflects processes of reprocessing that are based on syntactic and semantic aspects of the sentence.